Situational Logic Before Strategy: Antenarratives of Export Sustainability in Green MSMEs in Indonesia - Qadri, Resi Ariyasa; Indriastuti, Mila (Jati: Jurnal Akuntansi Terapan Indonesia, 2026)
Guided by the premise of situational logic before strategy, this study examines how export sustainability is enacted by green micro, small, and medium enterprises (MSMEs) as an emergent organizational process rather than as the adoption of predefined sustainability models. Data were collected through in-depth semi-structured interviews with MSME owner-managers engaged in export activities, complemented by documentary analysis of sustainability-related policies and MSME-related papers. Data analysis followed an interpretive and abductive approach, tracing fragmented practices and forward-looking accounts through the lenses of situational logic and antenarrative analysis. The findings show that export sustainability emerges through fragmented, provisional practices shaped by resource constraints, market dynamics, and institutional tensions. Rather than implementing coherent sustainability strategies, owner-managers enact sustainability through situated judgment, where practices precede formalization and coherence is constructed retrospectively through everyday sensemaking. Practically, the study suggests that sustainability support for exporting MSMEs should move beyond standardized models and instead recognize the situated conditions under which sustainability is enacted in organizational life.